Interrupting sexual violence: the power of law, education, and media - Shariff, Shaheen; Dietzel, Christopher (Confronting systemic omissions and impacts in educational policy, 2023)
"As a reflection of the iMPACTS Project, an international research partnership that investigates sexual violence at universities and in society, this edited collection is the first to take a multi-disciplinary approach to understanding and addressing sexual violence and gender-based violence in Canada. The first section of the book examines law/policy issues impacting universities, while the second section explores student activism and university responses to students' experiences of sexual violence. The third section examines sexual violence interventions through education and pedagogy, including an arts-based toolkit, a theatre production, and an international internship program. The fourth and final section focuses vulnerable communities, including online and in person as well as within legal, human rights, and social justice frameworks. While law and education are two major themes in this book, systematic and institutional discrimination are also examined. As such, this book emphasizes intersectional identities and the disproportionate effects of sexual and gender-based violence on marginalized communities. This book addresses policy makers, educators, students, workshop facilitators, archivists, theatre professionals, and members of the general public. This book could be a recommended reading in university level courses across arrange of subject areas including law, policy, education, gender studies, health, and sociology. This edited collection is unique in that it is focuses on the Canadian context and consolidates emerging research on sexual violence from a variety of disciplines"--